2015
DOI: 10.1016/s2213-2600(15)00139-3
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing for identification of Mendelian disorders in critically ill infants: a retrospective analysis of diagnostic and clinical findings

Abstract: Summary Background Genetic disorders and congenital anomalies are the leading causes of infant mortality. Diagnosis of most genetic diseases in neonatal and paediatric intensive care units (NICU and PICU) is not sufficiently timely to guide acute clinical management. We used rapid whole-genome sequencing (STATseq) in a level 4 NICU and PICU to assess the rate and types of molecular diagnoses, and the prevalence, types, and effect of diagnoses that are likely to change medical management in critically ill infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
447
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(487 citation statements)
references
References 51 publications
(83 reference statements)
16
447
2
Order By: Relevance
“…15 In a study of wholegenome sequencing in children retrospectively identified after an inpa tient stay in either the neonatal or pediatric inten sive care unit, a diagnosis was achieved in 57% (20/35) of cases. 11 These wholegenome sequencing studies required highthroughput sequencers, bioinformatics support, automation and experts in the field of translational genomics, resources that are not readily available to most diagnostic laboratories at this time. Another option, wholeexome sequencing, focuses on the protein coding regions of the approximately 22 000 human genes.…”
Section: Discussionmentioning
confidence: 99%
“…15 In a study of wholegenome sequencing in children retrospectively identified after an inpa tient stay in either the neonatal or pediatric inten sive care unit, a diagnosis was achieved in 57% (20/35) of cases. 11 These wholegenome sequencing studies required highthroughput sequencers, bioinformatics support, automation and experts in the field of translational genomics, resources that are not readily available to most diagnostic laboratories at this time. Another option, wholeexome sequencing, focuses on the protein coding regions of the approximately 22 000 human genes.…”
Section: Discussionmentioning
confidence: 99%
“…3,[31][32][33][34][35][36][37][38][39][40][41][42] Seven studies presented data on the costs of WES or WGS testing pathways, [24][25][26][27][43][44][45] and eight studies presented data on clinically relevant outcome measures for these tests. 5,6,[8][9][10][46][47][48] Of the eight full economic evaluations, two were CUAs 22,23 and six were CEAs, published between 2014 and 2017 in Australia (2), the United States (1), the UK (1), the Netherlands (1), and Canada (1). [18][19][20][21][28][29][30] Of these publications, the study by Soden et al 29 did not directly report WES costs but estimated Population unclear 2 (6) No study population 6 (17) WES, whole-exome sequencing; WGS, whole-genome sequencing.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven of these studies investigated WES; 5,6,[8][9][10]46,47 the eighth evaluated WGS. 48 Four publications used the traditional care pathway in the investigated condition as a comparator. 6,10,46,48 Three publications were retrospective analyses 6,47,48 and three were diagnostic studies, estimating the diagnostic yield of WES in a variety of conditions.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…BRCA-negative familial breast cancer), and even to screen healthy individuals for future planning and predictive outcomes. Though WES is not generally applied to newborns, in critically ill infants it has shown a high rate of diagnosis of genetic disorders that have a direct effect on management and outcome (Saunders et al, 2012;Willig et al, 2015).…”
Section: Discussionmentioning
confidence: 99%